Vertically ordered mesoporous silica film-assisted electrochemical cytosensor for the sensitive detection of HeLa cells - Zeng, Zisan; Zhao, Yang; Yang, Luoxing; Xi, Fengna; Su, Danke (Frontiers in Chemistry, 2023)
Designing fast and simple quantitative methods on cheap and disposable electrodes for the early detection of HeLa cells is highly desirable for clinical diagnostics and public health. In this work, we developed a label-free and sensitive electrochemical cytosensor for HeLa cell detection based on the gated molecular transport across vertically ordered mesoporous silica films (VMSFs) on the disposable indium tin oxide (ITO) electrode. As high affinity for a folate receptor existed on the membrane of HeLa cancer cells, folic acid (FA) functionalized VMSF could regulate the transport of electrochemical probe (Fe(CN)63−) by the specific recognition and adhesion of HeLa cells toward the VMSF surface. In addition, VMSF, served as a solid skeleton, is able to effectively prevent the direct contact of cells with the underlying electrode, remaining the underlying electrode activity and favoring the diffusion of Fe(CN)63−. Once specific adhesion of HeLa cells to the VMSF surface happens, Fe(CN)63− redox probe exhibits impeded transport in the silica nanochannels, ultimately resulting in the decreased electrochemical responses and realizing the quantitative determination of HeLa cells with a broad linear range (101–105 cells/mL) and a low limit of detection (4 cells/mL). The proposed electrochemical cytosensor shows a great potential application for the early diagnosis of cervical cancer.